Comparative Analysis of the Effectiveness of Cash Payment and Qris Payment - Juliandhani, Audie Fricylia (Asosiasi Ahli Administrasi Indonesia, 2022)
This study aims to analyze the effectiveness of cash and QRIS (Quick Response Code Indonesian Standard) payment methods in transactions at Bandung State Polytechnic. A total of 104 respondents, who were students using the Business Laboratory, were selected as the sample. A quantitative approach was employed using descriptive analysis, correlation, and linear regression methods. The results show no significant difference in effectiveness between cash payments and QRIS payments. Both methods are considered effective based on transaction speed, ease of use, and convenience. These findings indicate that while QRIS is gaining popularity, cash payments still play an important role in micro-transactions. The study suggests the need for strategies to enhance digital payment adoption without disregarding conventional payment systems.